Nitrogen and phosphorous effects on growth of stevia rebaudiana bertoni under light emitting diode (LED) / Fui Ying Tsan ... [et al.] - Fui, Ying Tsan; Ngilah, Emmelly Imbuh; Gundadon, Hendrynus; Janpen, Chananchida (Universiti Teknologi MARA, Sabah, 2021)
Studies on planting of Stevia rebaudiana, an important industrial crop that provides non-caloric sweeteners for the beverage sector, is lacking in an indoor controlled environment. In the present study, using a nutrient film technique, nitrogen (N) and phosphorous (P) levels needed for S. rebaudiana were determined. The plants were grown under light emitting diodes (LED) at 16h/8h light/darkness photoperiod in an air-conditioned laboratory. The results obtained indicated that in terms of growth performance and leaf production, the half strength Hoagland solution, where N was 100 mg L-1 and P was 15 mg L-1 , enabled the optimum gain in this crop. The results have implications for economic purposes.